To What Extent is the Motivation of Western Teachers Understood by School Leaders in a Boys' Elementary School in Saudi Arabia? - Mehrban, Saqib (2017)
This dissertation investigates the motivation of Western teachers in the Saudi Arabian education system. Qualitative data collection methods are used to understand the different realities experienced by teachers and leaders. The transformative aspect to this project recognises the stark power inequality between Western teachers and school leaders in Saudi Arabia. Documentary evidence, reflective journal entries, group and individual interviews, as well as questionnaires are all used to understand the state and management of teacher motivation in a Riyadh school. The results indicate that the only way school leaders effectively motivated teachers in the school studied, was through the provision of material rewards. A top-down culture of compliance and a lack of autonomy for teachers were serious demotivators, as was the lack of professional development (PD) provided without caveats. It is argued that the school would benefit by moving away from the unsustainable model of motivating teachers with material rewards. It is recommended that school leaders ought to involve and inspire teachers with a vision and boost intrinsic motivation by developing autonomous teachers. To raise morale, performance and motivation, the prevailing top-down culture should be reformed into a more democratic one, where teachers reciprocate the trust shown in them by leaders.